A knowledge management model for enhancing quality and performance of higher education institutions: insights from Oman. (2nd August 2019) - Al-Hemyari, Zuhair A.
The quality and performance of higher education institutions (HEIs) are crucial to the success of HEIs in the short and long run. In this paper, a knowledge management (KM) model for HEIs is developed and proposed as an appraising mechanism that can be used to identify and monitor the quality and performance areas that are important to HEIs. The conceptualisation and operationalisation of the KM model is also articulated extensively in this paper and tested rigorously using a sample of HEIs in the form of College of Applied Sciences (CASs) in Oman. The findings from the study, which produces important implications for the Ministry of Higher Education (MoHE) as well as for HEIs, generally supports the KM model as an appraising mechanism for identifying and monitoring the quality and performance of HEIs.